2014
DOI: 10.4111/kju.2014.55.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Selective α1A-Adrenoceptor Blocker Silodosin for Severe Lower Urinary Tract Symptoms Associated With Benign Prostatic Hyperplasia: A Prospective, Single-Open-Label, Multicenter Study in Korea

Abstract: PurposeTo evaluate the efficacy and safety of silodosin 8 mg once daily in a 12-week treatment of subjects with severe lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH).Materials and MethodsA total of 100 subjects from 10 urology centers in Korea were included in this study. The inclusion criteria were as follows: age ≥50 years, International Prostate Symptom Score (IPSS) ≥20, quality of life (QoL) score ≥3, urine volume ≥120 mL and maximal urinary flow rate (Qmax) <15 mL/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…But this finding is contraindicated in the study by Moon KH (mean 31.3, 31.7; p 0.9404). 19 In the present study, we found that there is definitive improvement in IPSS (mean 16.46±6.34, 10.66±3.84) (p=0.000) in PDE5I group alone. This is supported by the study conducted by Lee SW et al where SD was -5.97 and p value was <0.05.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…But this finding is contraindicated in the study by Moon KH (mean 31.3, 31.7; p 0.9404). 19 In the present study, we found that there is definitive improvement in IPSS (mean 16.46±6.34, 10.66±3.84) (p=0.000) in PDE5I group alone. This is supported by the study conducted by Lee SW et al where SD was -5.97 and p value was <0.05.…”
Section: Discussionsupporting
confidence: 57%
“…Moon KH et al in their study had shown similar results, where mean (11.2, 14.7) p<0.0001. 19 In the present study, there was significant improvement in PVR (mean 64.33±40.95, 33.52±18.94 (p = 0.001) with alpha blockers alone. But this finding is contraindicated in the study by Moon KH (mean 31.3, 31.7; p 0.9404).…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, the blockage of α1A adrenoreceptors results in prostatic and urethral smooth muscle relaxation and may improve the voiding symptoms. Yokoyama et al [18]demonstrated that the selective α1A-blocker silodosin exerts inhibitory effects on detrusor overactivity by modulating C-fibre afferent activity using animal models. Consequently, α1A-blockade can improve the storage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, silodosin proved to be effective and safe. 64 Nocturia in BPH/LUTS Among patients with BPH, approximately 85% experience two or more episodes per night. Several studies have shown the efficacy of silodosin in reducing nocturia.…”
Section: Voiding Dysfunction In Bph/lutsmentioning
confidence: 99%